2022
DOI: 10.1111/inr.12805
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric nurse‐sensitive outcomes: A systematic review of international literature

Abstract: Background: Nurse-sensitive outcomes are measures for improvement and evaluation of the quality of nursing care delivered. The specific outcomes that need to be measured will be determined by the patient population, as well as the field and scope of practice, in which nursing care is being delivered. Currently, there is no internationally agreed upon set of nurse-sensitive outcomes for pediatric nursing, which provides specialist care to infants, children, and young people. Aim: To identify and evaluate nurse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
2
0
2
Order By: Relevance
“…A Dutch study that explored sensitive outcome use by nurses concluded that there is a lack of information on how nurses can and should be supported by outcome measurement tools ( 10 ) . In pediatric nursing, a literature review presented a total of 57 sensitive outcomes for use in the specialty ( 11 ) . The conclusion of both studies highlights the need to reach international consensus to guarantee minimum standards for actions or at least national guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A Dutch study that explored sensitive outcome use by nurses concluded that there is a lack of information on how nurses can and should be supported by outcome measurement tools ( 10 ) . In pediatric nursing, a literature review presented a total of 57 sensitive outcomes for use in the specialty ( 11 ) . The conclusion of both studies highlights the need to reach international consensus to guarantee minimum standards for actions or at least national guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Estudo holandês que explorou a utilização de resultados sensíveis por enfermeiras concluiu que falta informações sobre como as enfermeiras podem e devem ser apoiadas por instrumentos de medidas de resultados (10) . Na área da enfermagem pediátrica, revisão de literatura apresentou um total de 57 resultados sensíveis para uso na especialidade (11) . Na conclusão de ambos os estudos, destaca-se a necessidade de alcançar consenso internacional para garantir padrões mínimos para as ações ou ao menos diretrizes nacionais.…”
Section: Inovações E Contribuições Do Conteúdo Dos Capítulos Da Normaunclassified
“…Un estudio holandés que exploró el uso de resultados sensibles por parte de los enfermeros concluyó que falta información sobre cómo los enfermeros pueden y deben recibir apoyo de los instrumentos de medición de resultados (10) . En el área de enfermería pediátrica, una revisión de la literatura presentó un total de 57 resultados sensibles para su uso en la especialidad (11) . En la conclusión de ambos estudios se destaca la necesidad de alcanzar consensos internacionales para garantizar estándares mínimos de actuación o al menos directrices nacionales.…”
Section: Innovaciones Y Aportes Del Contenido Introductorio De La Normaunclassified